2012
DOI: 10.1371/journal.pone.0043261
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivities and Parkinson's Disease: Delay Aversion Is Not Worsened by Deep Brain Stimulation of the Subthalamic Nucleus

Abstract: Deep Brain Stimulation (DBS) of the Subthalamic Nucleus (STN) improves motor symptoms in Parkinson's disease (PD), but can exert detrimental effects on impulsivity. These effects are especially related to the inability to slow down when high-conflict choices have to be made. However, the influence that DBS has on delay aversion is still under-investigated. Here, we tested a group of 21 PD patients on and off stimulation (off medication) by using the Cambridge Gamble Task (CGT), a computerized task that allows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 67 publications
3
12
0
Order By: Relevance
“…Similarly, negative results were reported by Torta et al (2012) who examined risk taking behavior and delay aversion, both characteristics of impulsivity, on the Cambridge Gambling task. STN DBS in PD had no effect on delay aversion or risk taking on this task.…”
Section: Discussionmentioning
confidence: 53%
“…Similarly, negative results were reported by Torta et al (2012) who examined risk taking behavior and delay aversion, both characteristics of impulsivity, on the Cambridge Gambling task. STN DBS in PD had no effect on delay aversion or risk taking on this task.…”
Section: Discussionmentioning
confidence: 53%
“…Impulsive participants may impulsively discount future reward, i.e., show increased delay discounting. The Cambridge Gambling Task (Rogers et al, 1999), used by Torta et al (2012), measures delay aversion, identifying subjects who repeatedly pick the initial bet offered, and results are here presented alongside studies of delay discounting, the measure of impulsive tendencies it most closely resembled.…”
Section: Impulsivity Measuresmentioning
confidence: 99%
“…Impulsivity scores on the Barratt Impulsiveness Scale (BIS-11, Patton and Stanford, 1995) were measured in six studies (total of 165 patients) comparing scores either between DBS On and Off conditions (Torta et al, 2012;Seinstra et al, 2016), or between DBS On and PD-patients On medication or healthy controls (Hälbig et al, 2009;Evens et al, 2015;Hagelweide et al, 2018;Irmen et al, 2019). One study reported significantly worse impulsivity scores in a DBS-group compared to healthy controls (Hälbig et al, 2009).…”
Section: Clinical Scalesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other than deficits in motor inhibition summarized in Table 3 and increased loss-chasing in a gambling task, 135 investigators have not found any detrimental effects of STN-DBS on other features of impulsivity and risk taking. 136,137 More direct and "causal" evidence of the role of the STN in inhibitory and executive control comes from a handful of studies of subthalamotomy in PD. Postsubthalamotomy deficits on the Stroop in 30% of the PD patients and deterioration in release from proactive inhibition on a memory test, with normal performance in 98% of the sample before and 50% of the sample after surgery, have been reported.…”
Section: Evidence From Experimental Studies Of Stn-dbs or Subthalamotmentioning
confidence: 99%